Taxation, foreign aid and political governance: figures to the facts of a celebrated literature - Simplice A. Asongu (African Governance and Development Institute (AGDI), 2014)
This paper puts figures to the facts of Eubank (2012), a recently celebrated paper in the Journal of Development Studies. We investigate the underpinning Somaliland-based hypothesis that foreign aid dilutes the positive role of taxation on political governance. The assessment is based on 53 African countries for the period 1996-2010. For more policy options, the dataset is disaggregated into fundamental characteristics of African development based on income-levels, legal origins, natural resources and landlockeness. While the Eubank hypothesis is invalid in baseline Africa, low-income and English common law countries of the continent, we cannot conclude on its validity for other fundamental characteristics of development. Policy implications, caveats and future directions are discussed.
Keywords: B20; F35; F50; O10; O55; 330; Foreign Aid; Political Economy; Development; Africa